Implications of the Dunning‐Kruger Effect for Counselors in Counseling Practice: A Systematic Review - Susanto, Eko; Novitasari, Yuni (Universitas Muhammadiyah Metro, 2024)
The Dunning-Kruger Effect phenomenon has long been in the spotlight in the field of cognitive psychology, describing a paradox in which individuals with low competence tend to overestimate their abilities. This article examines the implications of this phenomenon for counselors in counseling practice through a systematic review approach. By collecting and analyzing literature from various empirical and theoretical sources, this review aims to reveal how this cognitive bias affects the process of reflection, decision-making, and the effectiveness of counseling interventions. The results of the review indicate that the Dunning-Kruger Effect not only impacts the counselor's self-perception, but also affects the therapeutic relationship with the client through self-evaluation distortion and overconfidence. The practical implications of these findings emphasize the importance of metacognitive training, clinical supervision, and critical reflection in improving the quality of counseling services. This article concludes with recommendations for further research and the development of professional training modules to reduce the impact of cognitive bias in counseling practice.